An introduction to statistics for statistical genetics: general statistical concepts - O'Reilly, Paul (Henry Stewart Talks, 2017)
Summary measures: mean, variance, covariance and correlation, Fundamentals of statistics: models, estimation, hypothesis testing and prediction, Frequentist vs. Bayesian: genetic association testing, the ‘multiple testing problem’ and the permutation procedure